The Importance of Labor Market Regulation in Poverty Reduction - Bozarova Gulnora Gulamovna (Zien Journals, 2023)
This article shows that the market mechanism of the labor market is the population capable of working and willing to work for hire, as well as employers, the components of the labor market. The labor market mechanism is, based on the interaction and coordination of the multifaceted interests of unemployment and social benefits, and its role in reducing poverty among the population is, revealed
Keywords: Population employment; demography; migration policy